Hybrid PEMFC–battery systems for marine propulsion: Optimization of efficiency and operational safety - Ala'a Al-Falahat; Saad Alrwashdeh (International Journal of Renewable Energy Development, 2026)
This study presents a critical review and optimization of a hybrid proton exchange membrane fuel cell (PEMFC) battery propulsion system for marine operations under dynamic working conditions. The proposed system incorporates the most current energy management methods such as model predictive control (MPC) and eco-cooling processes to maximize system performance, efficiency, and safety of its work. The system performance is tested during a typical marine load profile and compared to a conventional PEMFC-only baseline configuration that operates without hybrid energy storage or with sophisticated control systems. The findings prove that the hybrid system shows a significant enhancement in operational performance with an increase in efficiency to up to 52.6 % and a significant reduction in hydrogen consumption during the transient load conditions. Moreover, battery support is also integrated to improve load-following capabilities, and minimizing stresses on the fuel cell stack, which is essential for enhanced durability and system reliability. In addition, the given solution enhances thermal control and safety levels because the operating temperatures are kept constant, and fluctuations in the system variables are quickly reduced. The Hybrid design also facilitates a better distribution of the energy and lower auxiliary losses, hence contributing to the greater stability of the system. These results show the potential of hybrid energy storage and enhanced control measures in enhancing the efficiency, sustainability, and safety of marine propulsion systems and can provide a promising avenue to decarbonized maritime energy systems.